1999
DOI: 10.1002/(sici)1096-9861(19990719)410:1<90::aid-cne8>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase-positive innervation is present at undifferentiated stages of the sea turtle Lepidochelis olivacea embryo gonads: Implications for temperature-dependent sex determination

Abstract: In embryos of different reptile species, incubation temperature triggers a cascade of endocrine events that lead to gonad sex differentiation. The cellular and molecular mechanisms by which temperature sets in motion this process are still controversial. Here, we begin evaluating the possible participation of the nervous system in temperature-dependent sex determination by showing the existence and origin of acetylcholinesterase (AchE)-positive nerve fibers in undifferentiated gonads of the Lepidochelys olivac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 54 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Several lines of research suggest additional roles for cholinergic systems in overall brain homeostasis and plasticity [19]. Further, barring few studies on the topographical distribution of acetylcholinesterase and butyrylcholinesterase activities in the diencephalon, mesencephalon and cerebral hemisphere of the adult lizard, Calotes versicolor [10,11]; in the different parts of the adult brain and cerebral spinal cord of Agama agama [20] and in neuronal fibers of the undifferentiated gonad of Lepidochelis olivacea [21], there are nil reports on the expression/presence of AChE activity in the developing embryos. Further, in the present investigation on the developing brain of C. versicolor a slight increase in AChE activity was noticed that remained relatively more or less the same until gonadal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of research suggest additional roles for cholinergic systems in overall brain homeostasis and plasticity [19]. Further, barring few studies on the topographical distribution of acetylcholinesterase and butyrylcholinesterase activities in the diencephalon, mesencephalon and cerebral hemisphere of the adult lizard, Calotes versicolor [10,11]; in the different parts of the adult brain and cerebral spinal cord of Agama agama [20] and in neuronal fibers of the undifferentiated gonad of Lepidochelis olivacea [21], there are nil reports on the expression/presence of AChE activity in the developing embryos. Further, in the present investigation on the developing brain of C. versicolor a slight increase in AChE activity was noticed that remained relatively more or less the same until gonadal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various neurotransmitters display a variety of trophic effects, when available during developmental stages, in various organs including the genital tract (Buznikov et al, 1999). Ac- cordingly, published evidence suggests that autonomic innervation might be required for cell differentiation, development, and structural integrity of various male reproductive tract organs (Hodson, 1965;Nagai et al, 1982;Gerendai et al, 1984Gerendai et al, , 1989Bergh et al, 1987;Zhu et al, 1998;Gutiérrez-Ospina et al, 1999;Chow et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, autonomic innervation is necessary to maintain mature ovary (Burden and Lawrence, 1977;Gerendai et al, 1978;Burden et al, 1981Burden et al, , 1983 and testicular functional and structural integrity (Hodson, 1965;Nagai et al, 1982;Bergh et al, 1987;Lamano-Carvalho et al, 1996;Zhu et al, 1998;Chow et al, 2000). It has also been suggested that autonomic innervation is even required for the process of gonadal sex determination and/or differentiation in some vertebrate species (Gutiérrez-Ospina et al, 1999). Taken together, these observations suggest that the autonomic innervation might control cell differentiation and development throughout the male reproductive tract.…”
mentioning
confidence: 97%